Changes in C-reactive protein， neutrophil-to-lymphocyte ratio， and hemoglobin levels in maintenance hemodialysis patients with tunnel catheter and arteriovenous fistula vascular access and their predictive values for infections - Wang Zi-jing; Zhong Jie; Gong Xue-feng; Ru Xue (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the differences in C-reactive protein（CRP）， neutrophil-to-lymphocyte ratio（NLR） and hemoglobin（Hb） levels in maintenance hemodialysis （MHD） patients with tunnel catheter and arteriovenous fistula（AVF） and their value in predicting infections.MethodsA total of 108 MHD patients from 1 January 2020 to 30 June 2022 were selected from Affiliated Hopital of Panzhihua College and grouped according to different vascular accesses. Forty-seven patients with tunnel catheter vascular access were included in the catheter group and 61 patients with AVF vascular access were included in the AVF group. Renal function indicators （serum creatinine ［Scr］， blood urea nitrogen ［BUN］）， dialysis adequacy （single ventricular urea clearance index ［spKt/V］， urea reduction ratio［URR］， post-equilibrium urea clearance index［eKt/V］）， CRP， NLR， Hb and incidence of infection were compared between the two groups at baseline and at 6-month follow-up. The predictive values of CRP， NLR and Hb levels for infections were analyzed.ResultsThere were no significant differences in Scr， BUN， spKt/V， URR， and eKt/V between the two groups at baseline and at 6 months follow-up（P>0.05）. At the 6-month follow-up， CRP （12.92 ± 3.17 mg/L vs. 16.35 ± 5.11 mg/L） and NLR（3.36 ± 0.74 vs. 4.57 ± 1.23） in the AVF group were significantly lower than those of the catheter group，while Hb（110.52 ± 12.16 g/L vs.100.31 ± 14.47 g/L） was significantly higher（P<0.05）. The incidence of infection in the AVF group was significantly lower than the catheter group（13.11% vs.31.91%， P<0.05）. At the 6-month follow-up， CRP（18.85 ± 5.09 mg/L vs.13.21 ± 3.36 mg/L） and NLR（5.60 ± 1.21 vs. 3.43 ± 1.08） in the infection group were significantly higher than those at baseline， while Hb（94.70 ± 11.96 g/L vs.109.16 ± 14.14 g/L） was significantly lower（P<0.05）. Receiver operating characteristic（ROC） curve results showed that the area under the curve（AUC） of a combination of CRP， NLR， and Hb in predicting MHD-related infection at 6 months of follow-up was 0.928（95% CI： 0.862-0.969）， with a sensitivity of 78.26% and a specificity of 91.76%， which was significantly greater than that of each indicator alone（P<0.05）. At the 6-month follow-up， the cut-off values of CRP， NLR， and Hb were divided into low and high levels. The risk of infection in patients with high levels of CRP and NLR at the 6-month follow-up was 7.180 times（95% CI： 2.623-19.656） and 4.750 times （95% CI： 1.730-13.043） higher than that in patients with low levels. The risk of infection in patients with low Hb levels was 5.567 times higher than that in patients with high Hb levels（95% CI： 2.272-14.085）（P<0.05）.ConclusionCompared with patients with a tunnel catheter vascular access， patients with an AVF vascular access have abnormal levels of CRP， NLR and Hb， and the incidence of infection is lower. The combination of CRP， NLR and Hb in predicting MHD co-infection has a good reference value， and can provide references for clinical evaluation of MHD infection.